Human Influenza A Virus (IAV) Decreases Mitochondrial Respiration of Infected MDCK Cell - M Derakhshan; GEN Kass; MJ Carter (Tehran University of Medical Sciences, 2005)
Studies of interaction between viruses and mitochondria have shown that they can affect the mitochondria and induce mitochondrial alterations. Sometimes this interaction leads to induction or inhibition of apoptosis in infected cells. Interaction between adenoviruses and mitochondria showed the first evidence that a viral infection could affect the cell and induces apoptotic process. In addition, linkage between human diseases and mitochondrial dysfunction has been revealed. A Previously work showed that poliovirus infection led to decrease in total cellular respiration induced by inhibition of mitochondrial electron transport chain. We have screened different human viruses to observe their effect on mitochondrial respiration using Oxygen Electrode (OE). Here we report the effect of influenza A virus (IAV) on mitochondrial cell respiration. The addition of antimycin A (AA) to respiring cells completely blocked cellular respiration that indicates nearly all of the cellular consumption of oxygen is attributed to the mitochondria. Our result showed human influenza A virus (IAV) decreases total cell respiration in infected MDCK cells.